2011
DOI: 10.1002/asna.201111624
|View full text |Cite
|
Sign up to set email alerts
|

Convection and differential rotation properties of G and K stars computed with the ASH code

Abstract: The stellar luminosity and depth of the convective envelope vary rapidly with mass for G-and K-type main sequence stars. In order to understand how these properties influence the convective turbulence, differential rotation, and meridional circulation, we have carried out 3D dynamical simulations of the interiors of rotating main sequence stars, using the anelastic spherical harmonic (ASH) code. The stars in our simulations have masses of 0.5, 0.7, 0.9, and 1.1 M , corresponding to spectral types K7 through G0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 31 publications
(41 reference statements)
6
66
1
Order By: Relevance
“…We generally found that for simulations with Ro < 1, meridional circulations possess many cells in radius and/or latitude per hemisphere. Only for anti-solar differential rotation cases, is the meridional circulation uni-cellular Matt et al (2011). We also find that the amplitude decreases as the rotational influence is increased as shown on Figure 4 right panel.…”
Section: Differential Rotation and Meridional Circulation In Starssupporting
confidence: 57%
See 2 more Smart Citations
“…We generally found that for simulations with Ro < 1, meridional circulations possess many cells in radius and/or latitude per hemisphere. Only for anti-solar differential rotation cases, is the meridional circulation uni-cellular Matt et al (2011). We also find that the amplitude decreases as the rotational influence is increased as shown on Figure 4 right panel.…”
Section: Differential Rotation and Meridional Circulation In Starssupporting
confidence: 57%
“…The ω-effect is a direct measure of the differential rotation ΔΩ established in the star. It is well known both theoretically and observationally that the differential rotation in the convective envelope of solar-type stars is directly connected to the star's rotation rate Ω 0 (Donahue et al(1996), Barnes et al(2005), Ballot et al (2007), Brown et al (2008), Küker et al(2011), Matt et al (2011), Augustson et al (2012), Gastine et al (2013)). However, the exact scaling exponent n r (i.e.…”
Section: Stellar Dynamo: Theoretical Conceptsmentioning
confidence: 98%
See 1 more Smart Citation
“…Such behavior is seen in both simulations of spherical domains and Cartesian domains at various levels of turbulence in both the ASH simulations (Brun & Palacios 2009;Matt et al 2011) and simulations carried out in Cartesian domains (Käpylä et al 2004), as well as in spherical segments (Käpylä et al 2011). We observe that this transition between solar-like and anti-solar-like differential rotations occurs within flows that have a Rossby number of nearly one.…”
Section: Scaling With Rotation and Massmentioning
confidence: 55%
“…The Rayleigh numbers at mid-convection zone are about 50 times the critical Rayleigh number (Jones et al 2009) for the Case A simulations and about 25 times for the Case B simulations. These levels of supercriticality are equivalent to ASH simulations of lower mass stars (e.g., Brown et al 2008;Matt et al 2011). The lower level of supercriticality in the 1.3 M simulations is primarily due to the stronger driving of the convection and larger superadiabatic gradient, both of which are in turn due to the higher luminosity and narrower convection zones of the higher mass F-type stars.…”
Section: Scaling Diffusion With Rotationmentioning
confidence: 61%